(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines 20th-century French literature, focusing on works written in the French language during that period. The literary developments of the time often paralleled shifts in the visual arts. Characterized by an element of entertainment and a degree of detachment from everyday life, French literature of the 20th century reflects a search for ideals. In this pursuit, French writers frequently looked to Russian literature as a source of inspiration and guidance. The evolution of French literature in this century was profoundly shaped by major historical events and the political, philosophical, moral, and artistic crises that defined the era.